Environmental summer camp in a Greek Island - Καραμπέρης, Μιχαήλ; Αποστολοπούλου, Σοφία; Κουνάνη, Αριστέα; Σκαναβή, Κωνσταντίνα; Γρηγόρογλου, Γαρυφαλιά (2021)
Nowadays, many researchers have proved that environmental summer camps could help children to become acquainted with nature and develop environmental values. This paper aims into analyzing a comprehensive thirty-day environmental summer camp- its operations and effectiveness in promoting responsible citizenship behavior. The instructional program is aimed at children between 6 to 13 years old, residing on Greek islands. This review examines an environmental summer camp on the island of Skyros, as a case study. The study incorporates participant survey data; interviews will be conducted with the attendees. The change of knowledge and environmental awareness, prior to and at completion of this summer camp, will be assessed. The goal of this project is to develop an environmental educational program that would be delivered as a summer camp and design the evaluation tools that would assess its effectiveness into shaping children’s environmental behavior